Effects of endothelial cell growth factor on bone remodelling in vitro. - Canalis, E (1987)
Endothelial cell growth factor (ECGF) alpha was studied for its effects on bone formation in cultured fetal rat calvariae and on bone resorption in cultured fetal rat long bones. ECGF at 0.1-100 ng/ml stimulated [3H]thymidine incorporation into DNA, an effect enhanced by heparin. Treatment with ECGF for 24 h decreased the incorporation of [3H]proline into collagen but treatment for 48-96 h increased collagen and noncollagen protein synthesis, an effect that was concomitant with an increase in DNA content. ECGF did not alter collagen degradation in calvariae or 45Ca release from long bones, which indicated it had no effect on bone resorption. Although ECGF increased prostaglandin E2 concentrations, its effect on DNA synthesis was not prostaglandin-mediated. In conclusion, ECGF stimulates calvarial DNA synthesis, which is an effect that results in a generalized increase in protein synthesis, but ECGF has no effect on matrix degradation or bone resorption.